Geometrical Model of bearing Capacity for a Safe Rectangular Vertically Loaded Shallow Pad Foundation on a Cohessionless (Sandy) Soil with Minimum Angle of Friction - Okeniyi, A.G.; Akolade, A.S.; Adefisoye, S.A.; Akanbi, O. T.; Okeleye, O.D. (International Journal of Advanced Engineering Research and Science, 2022)
Provision of adequate structural footing in building infrastructures is sensitive and highly challenging. Thus to alleviate the challenges of the subject task, a model was developed for simulating behavior of a pad rectangular footing on a cohessionless soil under the action of a vertical load. The approach is purely mathematical techniques of modeling, concept and application. A governing equation was theoretically formulated based on a specified condition, theories and applicable parameters. This was experimentally simulated to describe the relationship between variable parameters and to predict the geotechnical behaviour (bearing capacity) of the sandy soil underneath a shallow foundation. The geometry is specified by footing length, L, breadth, B and the placement depth, Df of the element. The model clearly established the interrelationship between the dominant parameters of the soil and footing geometry for determining bearing capacity to help engineering decisions in the design of a safe footing on a sandy soil environment.